Effect of complete feed blocks or grazing and supplementation of lambs on performance, nutrient utilisation, rumen fermentation and rumen microbial enzymes - S.K.S. Raghuvansi; R. Prasad; M.K. Tripathi; A.S. Mishra; O.H. Chaturvedi; A.K. Misra; B.L. Saraswat; R.C. Jakhmola (Animal, 2007)
A study to compare two feeding systems, stall feeding (SF) and grazing plus supplementation (GR) was carried out, based on intake, performance and rumen fermentation characteristics of lambs. While SF animals received ad libitum complete feed blocks (CFB), GR animals were allowed grazing for 8 h on a pasture and supplemented with concentrate mixture at 250 g per head per day. Intake in grazing animals was determined using chromium III oxide as internal marker. Intake of dry matter (DM), crude protein (CP) and organic matter (OM) were higher ( P < 0.01) in SF than in GR animals. Similarly, digestibility of OM, CP and energy were higher ( P < 0.01) in SF animals. Average daily gain in SF animals (101 g) was significantly ( P < 0.01) higher than in GR animals (78 g) but total wool yield was similar for the two groups (856 g, SF; 782 g, GR). The pH of the rumen content, concentration of total volatile fatty acids and total activities of carboxymethyl cellulase, xylanase and esterase in the rumen liquor were similar. The concentrations (mg/dl) of total nitrogen (125, SF; 63, GR) and NH3-nitrogen (42, SF; 31, GR) were higher in SF animals than that of GR animals. A significantly higher activity ( P < 0.05) of microcrystalline cellulase (24.5 v. 7.7 units) and lower activity ( P < 0.05) of protease (309 v. 525 units), was observed in the rumen of SF animals than in GR animals. SF animals could therefore harness more energy through degradation of plant cell walls thus reducing breakdown of plant proteins as gluconeogenic source. The SF system of feeding where CFB was offered to sheep appeared superior to GR in terms of intake, nutrient utilisation and animal performance. Therefore the SF feeding system where CFB are offered to animals can be advocated as an alternative to grazing and supplementation feeding strategy for sheep production, especially where the pastures are highly eroded and need resting for regeneration or curing. The CFB feeding can also be adopted under adverse conditions like drought and famine, a common phenomenon in arid and semiarid conditions.